Strong-lensing of Gravitational Waves by Galaxy Clusters. Issue Volume 13:Issue S338(2017) (29th January 2019) - Smith, Graham P.; Berry, Christopher; Bianconi, Matteo; Farr, Will M.; Jauzac, Mathilde; Massey, Richard; Richard, Johan; Robertson, Andrew; Sharon, Keren; Vecchio, Alberto; Veitch, John
Abstract: Discovery of strongly-lensed gravitational wave (GW) sources will unveil binary compact objects at higher redshifts and lower intrinsic luminosities than is possible without lensing. Such systems will yield unprecedented constraints on the mass distribution in galaxy clusters, measurements of the polarization of GWs, tests of General Relativity, and constraints on the Hubble parameter. Excited by these prospects, and intrigued by the presence of so-called "heavy black holes" in the early detections by LIGO-Virgo, we commenced a search for strongly-lensed GWs and possible electromagnetic counterparts in the latter stages of the second LIGO observing run (O2). Here, we summarise our calculation of the detection rate of strongly-lensed GWs, describe our review of BBH detections from O1, outline our observing strategy in O2, summarize our follow-up observations of GW170814, and discuss the future prospects of detection.